1999
DOI: 10.1007/bf02364371
|View full text |Cite
|
Sign up to set email alerts
|

Strength and relaxation properties of synthetic shoe thread

Abstract: Modem shoe manufacture requires the use of high-quality materials, including shoe thread. Shoe thread is exposed to significant mechanical effects during manufacture and wear and for this reason improving its service properties is very pressing.The strength and deformation properties of shoe thread of two types are compared here: the polyester fibre Lavsan, widely used in the industry, and Lavsan fibre modified by adding the viscose fibre Siblon. In addition, our studies were directed toward investigating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
Order By: Relevance
“…It was reported that simultaneous degradation and rebuilding of macromolecules was the reason for the property changes in polymers after O 3 treat- ment. 14,22 In our study, O 3 concentration was also a signi®cant factor and had a negative effect on TS and EB for LLDPE (p < 0.05). Also, the RH of O 3 gas had only a slight reducing effect on TS (p < 0.1).…”
Section: Mechanical Propertiesmentioning
confidence: 44%
See 1 more Smart Citation
“…It was reported that simultaneous degradation and rebuilding of macromolecules was the reason for the property changes in polymers after O 3 treat- ment. 14,22 In our study, O 3 concentration was also a signi®cant factor and had a negative effect on TS and EB for LLDPE (p < 0.05). Also, the RH of O 3 gas had only a slight reducing effect on TS (p < 0.1).…”
Section: Mechanical Propertiesmentioning
confidence: 44%
“…26 The observed increase in methyl content of O 3 -treated LLDPE in our study might indicate degradation of the polymer backbone. Other studies 13,14 also have reported chain scission for PE ®lms after O 3 treatment.…”
mentioning
confidence: 72%